An application of the SWICi board game in career decision intervention module for at-risk adolescents / Yusnita Ibrahim and Intan Syahriza Azizan - Ibrahim, Yusnita; Azizan, Intan Syahriza (Universiti Teknologi MARA Cawangan Kedah, 2022)
This article introduces the SWICi board game based on the underpinning Social Cognitive Career Theory. The SWICi board game is one of the activities in the Career Decision Intervention Module. The main objective of this SWICi board is game to assist at-risk adolescents in Malaysia to explore their career identity and knowledge in the world of work to increase efficacies in their career decision-making process. SWICi board game can be played individually or in groups of 2 to 6 adolescents. The development of SWICi board game of the Career Decision Intervention module for at-risk adolescents was validated by 10 experts. Then, a group of adolescents from 13 to 17 years was piloted to check the module’s reliability movement which ensue onward to a preliminary study. The pilot study demonstrated the process of validation for the Career Decision Intervention Module that contributes to the development of ‘best-practices’ in guiding adolescents’ career decision-making. The SWICi board game received favourable responses from adolescents that brought about a crucial outcome. In addition, brief implications and recommendations for future research and practices are provided.